2013
DOI: 10.1177/1460458213488382
|View full text |Cite
|
Sign up to set email alerts
|

Website design: Technical, social and medical issues for self-reporting by elderly patients

Abstract: There is growing interest in the use of the Internet for interacting with patients, both in terms of healthcare information provision and information gathering. In this paper we examine the issues in designing healthcare websites for elderly users. In particular this paper uses a yearlong case study of the development of a web-based system for self-reporting of symptoms and quality of life with a view to examine the issues relating to website design for elderly users. The issues identified included the technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Whilst not all required data ARE available from the patient EMR, studies have found varying results with as much as 69% of data required being found and used to prepopulate trial eCRFs . Discussions around the design and theoretical modelling of EMRs, eCRFs and ECD were prevalent within the included papers . The electronic systems reported vary in quality, with some being used in mock environments and others being purely theoretical.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst not all required data ARE available from the patient EMR, studies have found varying results with as much as 69% of data required being found and used to prepopulate trial eCRFs . Discussions around the design and theoretical modelling of EMRs, eCRFs and ECD were prevalent within the included papers . The electronic systems reported vary in quality, with some being used in mock environments and others being purely theoretical.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 The most common usability issues in our study were navigation, design and learnability which are consistent with the literature. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The most common usability issues in our study were navigation, design and learnability which are consistent with the literature. 20,21 Navigation is important to manoeuvre through multifaceted information on a website with accessing support groups and psychological well-being an easy task for participants. Although, locating further information content such as contact details was challenging.…”
Section: Discussionmentioning
confidence: 99%